Multipass Circular SAR 3D Imaging via L-based Complex Approximate Message Passing algorithm - Yang, Weixing; Zhu, Daiyin (2023 IEEE Radar Conference (RadarConf23), 2023)
Multipass circular synthetic aperture radar (MCSAR) three-dimensional (3D) imaging is a challenging problem. For anisotropic scattering observation targets, the strategy of subaperture incoherent 3D imaging is generally adopted. When the target is reconstructed along the elevation direction in the multipass circular SAR subaperture image stack, the reconstruction method via L_{q} -norm (0 < q < 1) regularization is proposed in this paper. In subaperture 3D target reconstruction, the L_{1/2} -based complex approximate message passing (CAMP) reconstruction algorithm combined with the Bayesian information criterion (BIC) is proposed in this paper. Combined with BIC, the estimation of the sparsity in elevation can be obtained, and the L_{1/2} -based CAMP algorithm can be used to reconstruct the target in elevation rapidly and accurately. Compared with the target reconstruction algorithm in elevation with multipass circular SAR data, such as the L_{1} norm-based method, the clear observed target 3D image with fewer desultory points can be obtained by the proposed method. Detailed experiments on real MCSAR data demonstrate the advantages of the proposed method.